Research on the Innovation Development of Luggage Brands and Products Driven by New Productive Forces - Hui WANG; Hui XIE (Pige Kexue Yu Gongcheng)
Driven by the new quality productivity, the luggage industry is facing opportunities for innovative development. This paper started with the definition and connotation of the new quality productivity, and introduced its innovation elements such as high efficiency, intelligence, networking, and sustainability. The current state of the luggage brand market was reviewed from three aspects: changes in consumer demand, market competition trend, and the impact of technological innovation. Based on the development of new quality productivity, innovative development paths were proposed for luggage brands in key areas such as materials, technology, user experience, and green sustainable development. This work provides new ideas for the future brand innovation and development of the luggage industry.